Le bilinguisme judiciaire au Québec - Prujiner, Alain (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1983)
The tradition of bilingual proceedings before Quebec courts is examined firstly, as to its historical development, and, secondly, as to the legal and sociological aspects of the question. Although the province of Quebec has since 1760 always permitted some form of bilingual representation at the judicial level, the legislature has pondered more than once during this period over the exact status the French language should enjoy in its courts. The author believes that the effectiveness of the present-day system depends largely upon the notion of individual, rather than institutionalized, bilingualism and that its future success lies in the willingness of the province's lawyers to meet the linguistic requirements of the courts. It has been proven that discriminatory linguistic policies lead necessarily to major conflicts. On the other hand, acceptance of the group's language rights will serve to reinforce its feeling of belonging to a social unit. However, it is the author's opinion that more than a coherent policy is needed to ensure the survival of a particular language in the courts.